1999
DOI: 10.1142/s0217751x99001536
|View full text |Cite
|
Sign up to set email alerts
|

U Duality and Network Configurations of Branes

Abstract: We explicitly write down the invariant supersymmetry conditions for branes with generic values of moduli and U-duality charges in various space-time dimensions D ≤ 10. We then use these results to obtain new BPS states, corresponding to network type structure of such branes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, the problem is being given attention to by scientists and researchers by means of use of recycled materials for the fabrication of composite materials. Another advantage of using recycled materials for composite fabrication is given relief to the non-renewable resource and getting rid of the scrap materials off the environment, apart from producing relatively low-cost materials [11,12,13]. By using complete https://doi.org/10.26434/chemrxiv-2023-5pg50-v2 ORCID: https://orcid.org/0000-0003-3607-0513 Content not peer-reviewed by ChemRxiv.…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem is being given attention to by scientists and researchers by means of use of recycled materials for the fabrication of composite materials. Another advantage of using recycled materials for composite fabrication is given relief to the non-renewable resource and getting rid of the scrap materials off the environment, apart from producing relatively low-cost materials [11,12,13]. By using complete https://doi.org/10.26434/chemrxiv-2023-5pg50-v2 ORCID: https://orcid.org/0000-0003-3607-0513 Content not peer-reviewed by ChemRxiv.…”
Section: Introductionmentioning
confidence: 99%
“…Among many of the discontinuous reinforcements used in Aluminum Matrix Composites (AMCs) glass particulate is one of the highly inexpensive and low-density reinforcements. Therefore, it inclusion in the composite lessens the cost as well as density of AMCs [6]. Madhusudan et al [7] reported the work on AMCs prepared by dispersing copper particulates as reinforcements in an Al matrix by means of stir-cast technique.…”
Section: Introductionmentioning
confidence: 99%
“…BPS string junctions preserve a quarter of the original supersymmetry (SUSY). String junction solutions have been obtained and used in a variety of situations in F-theory [2,3], M-theory [1,4] and string theories in ten and lower dimensions [5][6][7][8][9][10][11]. In this article we concern ourselves with such states and phenomena related to them in supersymmetric field theories, realised by D-branes in string theories [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%